[Translated article] Epidemic Scabies: New Treatment Challenges in an Ancient Disease - J.J. Lluch-Galcerá; J.M. Carrascosa; A. Boada (Elsevier, 2023)
Scabies which is among the most prevalent diseases worldwide, is becoming more frequent in Spain. The problems of this epidemic can be explained by several factors: improper application or prescription of treatments, resistance or reduced sensitivity to topical treatments, and poor understanding of the parasite and contagion. We require a new evidence-based approach to therapy that takes these problems into consideration. If symptoms persist after proper treatment, it is important to identify the reason for failure and standardize our approach. In refractory cases, the prescriber should prioritize oral medication, indicate a higher dose, combine treatments, or evaluate the use of off-label treatments in certain populations. The availability of new medications, such as spinosad or, especially, moxidectin, offer hope for bringing this disease under control. Resumen: La escabiosis es una de las enfermedades transmisibles más prevalentes en el mundo, actualmente en auge en nuestro entorno. Existen diferentes causas que explican la problemática de esta epidemia: una incorrecta aplicación o pauta del tratamiento; la disminución de la sensibilidad o la resistencia al tratamiento tópico y las carencias en el conocimiento del parásito y su transmisibilidad. Por este motivo es necesario un nuevo enfoque en el tratamiento de esta enfermedad que contemple los problemas y la evidencia actual. Si hay una persistencia de la clínica tras un correcto tratamiento es importante corroborar el fracaso terapéutico y estandarizar la actitud. Por último, ante un caso recalcitrante cabría plantear la posibilidad de priorizar el tratamiento oral, aumentar su dosis, realizar tratamientos combinados o plantear su uso fuera de ficha técnica en poblaciones especiales. La aparición de nuevos tratamientos, como el spinosad o, sobre todo, la moxidectina, aportan esperanza en el control de esta enfermedad.